Optimization Of Local Tax Revenue: A Case Study Of Local Tax Revenue In The South Sulawesi Province - Yusriah Amaliah; Ahmad Rosandi Sakir; Juwita Pratiwi Lukman (PT. Hafasy Dwi Nawasena, 2023)
This research investigates the optimization of tax revenue in South Sulawesi Province, focusing primarily on Motor Vehicle Tax, Vehicle Transfer Fee Tax, Surface Water Tax, Motor Vehicle Fuel Tax, and Cigarette Excise Tax. The study emphasizes the vital role of taxes in supporting regional income for infrastructure development and public services. It employs a qualitative descriptive research method and is conducted at the Regional Revenue Agency of South Sulawesi Province. The adoption of technology is acknowledged as a key success factor in improving tax collection efficiency. Results indicate a positive impact of policies enhancing public compliance with tax payments. Economic challenges and the COVID-19 pandemic underscore the need for more effective communication and education strategies, along with strengthened collaboration. In conclusion, this research recommends a collaborative approach, intensive educational campaigns, and technology utilization to improve tax compliance, providing valuable guidance for policymakers in South Sulawesi Province to optimize revenue.